Hubungan Antara Kohesivitas Kelompok dengan Social Loafing pada Tugas Kelompok yang Dilakukan Mahasiswa Universitas Negeri Padang - Fifi Wahyuni (Ranah Research : Journal of Multidisciplinary Research and Development, 2022)
This study aims to look at the relationship between group cohesiveness and social loafing in group assignments carried out by Padang State University students. This study uses a correlational quantitative design. Sampling in this study uses a purposive sampling technique. The subjects of this study were 110 students from Padang State University. Data were analyzed using product moment correlation and obtained r = -0.615 and p = 0.00 (p <0.05). These results indicate that there is a significant negative relationship between group cohesiveness and social loafing in group assignments carried out by Padang State University students.